Teacher Actions: The Influence on Entrepreneurial Behavioral Characteristics of Students - Silvana Bortoluzzi-Balconi; Deoclécio Junior Cardoso-da Silva; Italo Fernando Minello; Luis Felipe Dias-Lopes; Luciano Amaral (Revista Electrónica Educare)
Aims. This study aimed to identify the activities teachers from a Brazilian public higher education institution developed to analyze how these activities influenced undergraduate students’ entrepreneurial behavioral characteristics (EBCs). Method. The study applied a mixed method; the quantitative approach used the EBCs measurement instrument (Mansfield et al., 1987), analyzed with the Analytic Hierarchy Process (AHP), prioritizing the most important EBCs in the perception of 792 students. The qualitative approach implemented a semi-structured interview script and content analysis. This approach identified the activities teachers developed and characterized as distinct according to students’ perception and their relationship with the EBCs. Discussion. Thus, it was possible to identify that practical activities and those aimed at student autonomy, directed towards reality, with correlations between disciplines, and with interactive participation, dialogue, favorable environment and learning through experience, converge to developing the entrepreneurial characteristics of the students and are being carried out in the classroom. It was also found that commitment was the most evident characteristic. Conclusions. It can be concluded that the institution presents a promising scenario to develop entrepreneurial education. However, the activities currently carried out in the establishment are not efficient or sufficient since, at the same time, as the existence of entrepreneurial activities was proved, the students presented some unsatisfactory EBCs. Therefore, a longitudinal cut is suggested to analyze the EBCs and better understand the students’ evolution with the insertion of these practices in the classroom.